BUZZ GROUP METHOD TO ENHANCE COOPERATION AMONG STUDENTS IN CLASSROOM - Firda Fadhilah Muzanni Lubis; Aisyah Risti Wardani; Yunita Mutiara Harahap (English Education Study Program FKIP Universitas Alwashliyah Medan, 2023)
This article describes the concept of using buzz group in classroom to enhance cooperation among students. Buzz group can be alternative method employed by educators (teachers or lecturers) to maximize small group work classroom activity. Buzz group can be applied by students to solve problems given during learning activities. By using buzz group, it is expected that each students has chance to share information each other in a small group work. Thus, the students can be acknowledged for their individual and group strength when they explore a topic given in a limited time.